The Sportsman: On Hunting, a Sportsman's Manual, Commonly Called Cynegeticus - Xenophon, 432 BCE-351? BCE; Dakyns, Henry Graham, 1838-1911 (Salt Lake City, UT : Project Gutenberg, 1998)
"The Sportsman: On Hunting, a Sportsman's Manual, Commonly Called Cynegeticus" by Xenophon is a treatise written in ancient Greece. This practical manual guides hunters through the pursuit of game, from hares to wild boars and beyond. Xenophon details everything from selecting and training hounds to proper equipment and seasonal strategies. Yet hunting here means more than sport$1 (Bit shapes character, sharpens the senses, and prepares men for war. The work blends technical instruction with philosophical reflection on virtue, discipline, and excellence. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Cynegeticus
Release date is 1998-01-01
Produced by John Bickers, and David Widger
Keywords: Classical literature; Sportsmanship -- Early works to 1800